2009
DOI: 10.1111/j.1365-2478.2008.00734.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐frequency microtremor anomalies at an oil and gas field in Voitsdorf, Austria

Abstract: A B S T R A C TResults of a passive microtremor survey at an oil and gas field in Voitsdorf, Austria, are presented. The survey consists in six parallel profiles approximately 9 km long over two hydrocarbon reservoirs. For each profile the seismic wavefield was recorded synchronously at 11 in-line stations. The measurements were conducted with broadband seismometers and lasted, for each profile, at least 12 hours overnight. Data interpretation is based on a comprehensive data set and on the analysis of four di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(72 citation statements)
references
References 34 publications
2
69
1
Order By: Relevance
“…1) and is therefore expected to be strongly affected by anthropogenic signals. In fact, Lambert et al (2009) have already suspected (based on results of the 2007 data) that this anomaly is caused by a strong and unstable source, possibly related to cultural activities. This view is now supported with the more comprehensive data-set of 2008.…”
Section: Tablementioning
confidence: 93%
See 4 more Smart Citations
“…1) and is therefore expected to be strongly affected by anthropogenic signals. In fact, Lambert et al (2009) have already suspected (based on results of the 2007 data) that this anomaly is caused by a strong and unstable source, possibly related to cultural activities. This view is now supported with the more comprehensive data-set of 2008.…”
Section: Tablementioning
confidence: 93%
“…4b, suggest that some stations exhibit elevated V/H-amplitudes around 2 Hz. It was suggested that these or similar features could carry information on reservoir-related modifications in the wave-field (Dangel et al, 2003;Lambert et al, 2009;Saenger et al, 2009;van Mastrigt and Al-Dulaijan, 2008). Four spectral seismic attributes are used in this study to quantitatively describe these features and to map their distribution in space and time.…”
Section: Features Of Interestmentioning
confidence: 98%
See 3 more Smart Citations